Role of an Atypical Cadherin Gene, Cdh23 in Prepulse Inhibition, and Implication of CDH23 in Schizophrenia. (17th February 2021) - Balan, Shabeesh; Ohnishi, Tetsuo; Watanabe, Akiko; Ohba, Hisako; Iwayama, Yoshimi; Toyoshima, Manabu; Hara, Tomonori; Hisano, Yasuko; Miyasaka, Yuki; Toyota, Tomoko; Shimamoto-Mitsuyama, Chie; Maekawa, Motoko; et al.
Abstract: We previously identified quantitative trait loci (QTL) for prepulse inhibition (PPI), an endophenotype of schizophrenia, on mouse chromosome 10 and reported Fabp7 as a candidate gene from an analysis of F2 mice from inbred strains with high (C57BL/6N; B6) and low (C3H/HeN; C3H) PPI levels. Here, we reanalyzed the previously reported QTLs with increased marker density. The highest logarithm of odds score (26.66) peaked at a synonymous coding and splice-site variant, c.753G>A (rs257098870), in the Cdh23 gene on chromosome 10; the c.753G (C3H) allele showed a PPI-lowering effect. Bayesian multiple QTL mapping also supported the same variant with a posterior probability of 1. Thus, we engineered the c.753G (C3H) allele into the B6 genetic background, which led to dampened PPI. We also revealed an e-QTL (expression QTL) effect imparted by the c.753G>A variant for the Cdh23 expression in the brain. In a human study, a homologous variant (c.753G>A; rs769896655) in CDH23 showed a nominally significant enrichment in individuals with schizophrenia. We also identified multiple potentially deleterious CDH23 variants in individuals with schizophrenia. Collectively, the present study reveals a PPI-regulating Cdh23 variant and a possible contribution of CDH23 to schizophrenia susceptibility.